Lichen Sclerosis is Associated With a High Rate of Local Failure After Radio(chemo)therapy for Vulvar Cancer. Issue 1 (January 2022) - Fokdal, L.; Jensen, P.T.; Wulff, C.; Sanggaard, M.A.; Hae, M.; Niemann, I.; Hansen, E.S.; Lindegaard, J.C.
Abstract: Aims: Radio(chemo)therapy plays an important role in the treatment of vulvar cancer, either as postoperative treatment or as definitive treatment in patients who present with inoperable disease. Only limited data are available regarding outcome after modern state of the art radio(chemo)therapy and more information regarding prognostic factors are warranted. The aim of this study was to evaluate disease outcomes after radio(chemo)therapy in patients with vulvar cancer with special emphasis on the impact of lichen sclerosis on local control. Materials and methods: All consecutive patients ( n = 109) from the western half of Denmark who were treated with definitive ( n = 52) or postoperative ( n = 57) radio(chemo)therapy between January 2013 and January 2020 were included. Local control, cause-specific survival and overall survival, as well as morbidity, were analysed using Kaplan–Meier statistics. Prognostic factors for local control were analysed in univariate and multivariate analysis. Results: At a median follow-up of 35 (4–95) months, 46 (42.0%) patients were diagnosed with recurrence. Eighty per cent of the recurrences were located to the vulva region, leading to a 5-year local control of 58.9% (confidence interval 47.9–69.9). Cause-specific survival was 62.9% (confidence interval 53.1–72.7), whereas overall survival was 58.0% (confidence interval 47.6–68.5). Grade 3–4 morbidity was diagnosed in 10 (9%) patients. Lichen sclerosis (hazard ratio 3.89; confidence interval 1.93–7.79) was an independent risk factors for local recurrence. Patients without lichen sclerosis had a 5-year local control rate of 83.6% (confidence interval 67.2–99.0) and 62.6% (confidence interval 43.2–82.0) after postoperative and definitive radio(chemo)therapy, respectively. In patients with lichen sclerosis, the local control rate was 44.0% (confidence interval 19.3–69.0) and 17.6% (confidence interval 0–30.0) after postoperative and definitive radio(chemo)therapy, respectively. Conclusion: Radio(chemo)therapy plays an important role in the treatment of vulvar cancer. However, despite dose escalation, a substantial proportion of patients experienced local relapse. Pre-existing lichen sclerosis seems to have a significant impact on the risk of recurrence. This should influence surveillance programmes for these patients. Highlights: Patients received state of the art radio(chemo)therapy with MRI and PET-CT for contouring and dose planning. Prescribed dose was 64 Gy to the gross tumour volumes and 50–51.2 Gy to elective volumes. Recurrences after radio(chemo)therapy were mainly locally with involvement of the vulvar region. Pre-existing lichen sclerosis was the most important risk factor for local recurrence. Close surveillance programmes should be available for early detection of local recurrence for salvage surgery.